2020
DOI: 10.4038/cbj.v11i1.58
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Risk Tolerance in the Relationship between Financial Literacy and Investment Performance

Abstract: The main objective of this research paper is to study the impact of financial literacy on investment performance, with the mediating effects of risk tolerance. Data was collected using a standardised questionnaire from 203 individual investors in Chennai, India and the results indicate that there is a significant positive relationship between financial literacy and investment performance while the level of risk tolerance is partially mediating that relationship. This study is the first of its kind which has ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
0
9
3
1
Order By: Relevance
“…These research results contradict Bairagi & Chakraborty (2018); Kanagasabai and Aggarwal (2020), who found that age didn't significantly affect investors' risk perception in decision making.…”
Section: The Effect Of Age On Investment Decisions Through Perception...contrasting
confidence: 61%
“…These research results contradict Bairagi & Chakraborty (2018); Kanagasabai and Aggarwal (2020), who found that age didn't significantly affect investors' risk perception in decision making.…”
Section: The Effect Of Age On Investment Decisions Through Perception...contrasting
confidence: 61%
“…According to Abreu (2014), the existence of anchoring means that investors make an evaluation about their own anchor and adapt to an evaluation. When making decisions, the propensity to adhere towards one bit of information is regarded as Anchoring (Kanagasabai and Aggarwal 2020). One of the described phenomenon's is herding, pertaining to which investors appear to disregard their own private views and follow trading behavior of their equivalents (Aharon 2020).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…For those older Malaysians retire with insufficient savings, it may motivate them to take higher risk and seek for investment with higher returns. As a result, financial risk tolerance has been a prominent study in issues related to financial management, investment and investor's investment decisions (Nguyen et al, 2016;Chng & Hafinaz, 2019;Kanagasabai & Aggarwal, 2020). Many studies have cited and defined financial risk tolerance as the maximum degree of uncertainty of an individual's willingness to accept risk or uncertainties when he or she is making a decision (Roszkowski & Grable, 2010;Nobre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have cited and defined financial risk tolerance as the maximum degree of uncertainty of an individual's willingness to accept risk or uncertainties when he or she is making a decision (Roszkowski & Grable, 2010;Nobre et al, 2018). For example, risk-taking investors tend to consider more risky investments, thus indicating a relationship between financial risk tolerance and investment decisions (Nguyen et al, 2016;Kanagasabai & Aggarwal, 2020). Previous studies can further support the influence of financial risk tolerance towards decision-making as it has been widely studied over the years (Shtudiner, 2018;Chng & Hafinaz, 2019;Aeknarajindawat, 2020).…”
Section: Introductionmentioning
confidence: 99%